Legal Liability of Land Deed Officials in the Era of Electronic Land Title Certificates - Riza Zulfikar (Sean Institute, 2025)
This study examines the legal liability of Land Deed Officials in the era of electronic land title certificates, focusing on the challenges arising from digital transformation in land administration. The main problem lies in the inadequacy of existing legal frameworks to address system-based errors, cybersecurity risks, and the distribution of liability among multiple actors. Accordingly, this research aims to analyze the shift in liability concepts, evaluate the sufficiency of current regulations, and propose adaptive legal solutions. The study employs a normative juridical method with a descriptive-analytical approach, relying on statutory regulations, legal doctrines, and relevant scholarly literature. The findings reveal a significant transformation from individual, document-based liability toward a system-dependent and multi-actor model, where responsibility is shared among officials, government institutions, and system providers. However, the absence of clear legal boundaries creates uncertainty and potential unfairness, particularly when errors originate from digital systems. Furthermore, professional responsibility has expanded to include technological competence, making digital literacy an essential component of due diligence. The study emphasizes the need for regulatory reform to establish a comprehensive and adaptive legal framework. The adoption of a proportional multi-actor liability model, strengthening cybersecurity systems, and enhancing continuous professional training to ensure legal certainty, accountability, and fairness in digital land administration